Системний підхід до менеджменту фінансових ризиків - Kuznietsova, Nataliia V.; Bidyuk, Petro I. (The National Technical University of Ukraine "Igor Sikorsky Kyiv Polytechnic Institute", 2018)
The principles, methods, procedures and means of a system approach to risk analysis and management were studied. The article presents internationally well-known standards for risk management of various types and shows the classification of financial risks ratings. Using banking risks as an example, the existing standards are compared and it is shown how it is possible to present existing rating approaches in the unified structural table and how to estimate the probability interval of a financial risk occurrence. The main features and characteristics of the "risk" category as well as qualitative and quantitative characteristics are shown. Also, the formalization of risk tolerance and acceptance of risk and their interrelation is shown. On the basis of the existing international approaches to risk management the system methodology for the risk analysis and management based on the main principles and methods of the system approach is proposed. This methodology takes into account the basic characteristics and special features of financial processes development, processing of different types of uncertainties associated with the peculiarities of financial data, international practice, and includes new combined methods for minimizing financial risks.